Inventarisasi Ikan dan Kondisi Habitat di Danau Hanjalutung Kalimantan Tengah - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
The experiment was conducted in Lake Hanjalutung, Village Petuk Katimpun, Palangka Raya city. This study aims to document and inventory the species of freshwater fish are caught and determine its relevance to habitat conditions in Lake Hanjalutung. Methods of sampling carried out by setting 5 (five) observation station. Results of the study found 20 species of fish from 6 families. Most fish species are in the family Cyprinidae. Key words : Inventory of fishes, habitat conditions, Lake Hanjalutung.